Coronary heart disease prevention: a handbook for the health-care team - Lindsay, Grace M.; Gaw Allan (Edinburgh Churchill Livingstone, 2004)
Offers practical advice on correcting factors related to coronary heart disease through lifestyle and medical management
Keywords: Coronary heart disease-Handbooks, manuals; Coronary heart disease -- Risk factors -- Handbooks, manuals